EFFICACY OF FLUCONAZOLE TO TREAT OTOMYCOSIS IN CHILDREN - V.N. Yabloneva (Union of pediatricians of Russia, 2006)
In article are persented the results of clinical study of efficacy of fluconazole (mucoflucan) used to treat otomycosis in children. According to the results of the study fluconazole has effectively surpressed the mycotic infection and ameliorated symptoms of the disease, promoting earlier recovery. Key words: otomycosis, treatment, children, fluconazole.